THE ROLE OF ENTREPRENEURSHIP IN COMBATING POVERTY - Fozilov Vahobjon Akrom o’g’li (TADQIQOTLAR, 2026)
Annotation. This article examines the role of entrepreneurship in combating poverty and promoting sustainable economic development. The study analyzes how entrepreneurial activity contributes to employment generation, income growth, innovation, and improvement of living standards. Special attention is given to small and medium-sized enterprises, digital entrepreneurship, financial inclusion, and government support mechanisms. The article also evaluates the relationship between entrepreneurship development and poverty reduction using statistical and comparative analysis.